CHARACTERISTICS OF THE PRINCIPLE OF EXAMINING THE FACTS OF THE CASE EX OFFICIO - Khachikyan, Tigran (State and Law, 2022)
The following article is devoted to the principle of examining the facts of the case ex officio, which emphasizes the features of administrative court procedure. Consequently, the active role of the court in administrative procedure when stipulating the principle of examining the facts of the case ex officio is being discussed. Specifically, when resolving the dispute between the participants of public relations the court eliminates the factual inequality between the citizen and the public authority.
Keywords: administrative act; void; invalid; the principle of clarifying the factual circumstances of the case officially; public relations; administrative court procedure; «ex officio»; claim; case